Identification of hub genes and biological mechanisms underlying the pathogenesis of asthenozoospermia and chronic epididymitis - Chen, Yinwei; Sun, Taotao; Gu, Longjie; Ouyang, Song; Liu, Kang; Yuan, Penghui; Liu, Chang (Frontiers in Genetics, 2023)
Objective: Asthenozoospermia (AZS) is one of the most common causes of male fertility, affecting family well-being and population growth. Chronic epididymitis (CE) is a common and lingering inflammatory disease in the scrotum. Inflammation in the epididymis has a severe impact on sperm motility. This study aimed to explore the genetic profile and critical pathways involved in the pathological mechanisms of AZS and CE, and discover potential biomarkers. Methods: Genomic datasets of AZS and CE were obtained from the Gene Expression Omnibus (GEO) database, and relevant differentially expressed genes (DEGs) were identified. GO and pathway enrichment analyses, construction of a protein-protein interaction network, and receiver operator characteristic curve analysis were conducted. The expression profile of hub genes was validated in immunohistochemical data and testicular cell data. Immune infiltration, miRNA-hub gene interactions, and gene-disease interactions were explored. The mRNA levels of hub genes were further measured by qRT-PCR. Results: A total of 109 DEGs were identified between the AZS/CE and healthy control groups. Pathways of the immune system, neutrophil degranulation, and interleukin-4 and interleukin-13 signaling were enriched in AZS and CE. Five hub genes (CD300LB, CMKLR1, CCR4, B3GALT5, and CTSK) were selected, and their diagnostic values were validated in AZS, CE, and independent validation sets (area under the curve > 0.7). Furthermore, the five-hub gene signature was well characterized in testicular immunohistochemical staining and testicular cells from healthy controls. Immune infiltration analysis showed that infiltration of CD8+ cells and T helper cells was significantly related to the expression level of five hub genes. In addition, a miRNA-hub gene network and interaction of other diseases were displayed. The mRNA levels of hub genes (CD300LB, CMKLR1, CCR4, and B3GALT5) were significantly elevated in the patient group. The mRNA level of CTSK also showed a similar trend. Conclusion: Our study uncovered the genetic profile involved in AZS and CE, and elucidated enriched pathways and molecular associations between hub genes and immune infiltration. This finding provides novel insight into the common pathogenesis of both diseases as well as the potential biomarkers for CE-associated AZS.